(untitled) (KONFERENSIYA, 2025)
The work analyzes Uzbek culture-bound expressions—idioms, proverbs, and culturally specific terms—and the challenges they pose in English translation. Because many Uzbek expressions carry cultural and emotional meanings with no direct English equivalents, the study discusses strategies such as cultural substitution, descriptive translation, and functional equivalence. The annotation emphasizes the role of cultural knowledge in achieving accurate and meaningful translation between Uzbek and English